Hal Koch: Kirkehistoriker – demokrat – brobygger - Schjørring, Jens Holger (Dansk Teologisk Tidsskrift, 2012)
: On May 25, 2012 Tine Reeh defended her doctoral thesis at the University of Copenhagen on the Danish church historian, Hal Koch (1904-1963). Koch was an important fi gure in modern Danish history, not only as a theologian, but also as a pioneering innovator in adult education and nation-building during the Nazi occupation of Denmark. I start out paying tribute to Tine Reeh’s accomplishments, not least for presenting a full-scale analysis of Hal Koch within the general framework of his time. At the same time some viewpoints in her account are questioned. Tine Reeh maintains that the German dialectical theology and its Danish parallel, Tidehverv, had a particular impact on Koch. She presents a detailed picture of Koch’s monographs on Origen, on the relationship between church and state in medieval Denmark, and on Grundtvig, seen in interaction with Koch’s position as Lutheran theologian and preacher. The analysis of Koch’s activity during the years of German occupation has rightly been given particular attention. Yet, it is misleading to perceive 1945 as the year of conclusion. In the post-war period Koch presented several examples of a remarkable reorientation. Accordingly it is more appropriate to consider him a bridge-builder between church and society than to push him into the narrow confi nes of academic school theology.